2007
DOI: 10.1016/j.atherosclerosis.2006.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces IL-6 expression and the Jak-STAT3 pathway in aortic adventitia of LDL receptor-deficient mice

Abstract: Angiotensin II (A-II), the major effector peptide of the renin angiotensin system potently accelerates progression of atherosclerosis. To investigate its effects on vascular inflammatory mechanisms, we elucidated vascular cytokine expression during early lesion development in A-II-infused atherosclerosis-prone LDLR −/− mice. Male LDLR −/− mice were placed on a "Western" high-fat diet for 4 weeks, followed by sham or A-II infusion for 7 weeks. Equal blood pressures and elevations in serum lipids were seen in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 45 publications
4
104
0
4
Order By: Relevance
“…The results were similar, with enhanced IL-6 secretion observed in the older animals ( Figure 1C). Importantly, cytokine secretion was apparently independent of the presence of vascular hemorrhage; in fact, we previously have shown that cytokines are produced and secreted locally using in situ hybridization and time series analysis of aortic explants (29,39,40). Similarly, Ang II induced a significant, 2-fold increase in MCP-1 secretion in young animals and an enhanced, 4.7-fold increase in the older animals ( Figure 1C).…”
Section: Ang II Infusion Induced Aortic Dissection and Cytokine Secrementioning
confidence: 82%
See 2 more Smart Citations
“…The results were similar, with enhanced IL-6 secretion observed in the older animals ( Figure 1C). Importantly, cytokine secretion was apparently independent of the presence of vascular hemorrhage; in fact, we previously have shown that cytokines are produced and secreted locally using in situ hybridization and time series analysis of aortic explants (29,39,40). Similarly, Ang II induced a significant, 2-fold increase in MCP-1 secretion in young animals and an enhanced, 4.7-fold increase in the older animals ( Figure 1C).…”
Section: Ang II Infusion Induced Aortic Dissection and Cytokine Secrementioning
confidence: 82%
“…To establish the vascular cytokine response to Ang II infusion, aortic explants from young (<2 months old) and older (7-10 months of age) mice after 10 days infusion were prepared and cytokine secretion analyzed (29). Analysis of IL-6 secreted by the total aorta revealed a 3.7-fold increase in production in the young mice and a greater, 6.3-fold increase in the older mice (P < 0.001, 2-way ANOVA; Figure 1C).…”
Section: Ang II Infusion Induced Aortic Dissection and Cytokine Secrementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in wild type mice, Ang II infusion potently induces IL-6 expression in the aorta, making IL-6 the most abundantly secreted cytokine that has yet been detected. IL-6 is predominantly expressed by fibroblasts and activated macrophages in the adventitia, with lesser amounts in the media and intimal layers (Recinos, et al, 2007). IL-6 signaling pathway was locally activated in Ang II-induced aortic aneurysms (Tieu, et al, 2009),where its action promotes monocytic activation and adventitial macrophage accumulation via a chemokine MCP-1-CCR2-based mechanism (Ishibashi, et al, 2004;Tieu, et al, 2009).…”
Section: Vascular Inflammatory Actions Of Ang Ii-induced Nf-κb Signalingmentioning
confidence: 99%
“…IL-6 leads to the recruitment of circulating leukocytes and macrophages into the vascular wall, thereby leading to oxidation of lipoprotein, and atherogenesis [21] . It has been shown that Ang Ⅱ infusion induces IL-6 production, which results in atherogenesis and vascular diseases [102] . IL-6 is an NF-κB targeted gene.…”
Section: Gpcr/carma3/nf-κb Signaling Axis In Atherogenesismentioning
confidence: 99%